Perbedaan pengaruh hypnotherapy teknik direct suggestion dan teknik regression terhadap tingkat stres atlet pencak silat pasca pandemi Covid-19 (Studi komparatif ditinjau dari perspektif jenis kelamin pada atlet di Kabupaten Ngawi) - Rosyideva Yulienugroho; Muchsin Doewes; Sri Santoso Sabarini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to determine the effect of Hypnotherapy Direct Suggestion technique and Hypnotherapy Regression technique on the stress level of male and female athletes of martial arts in Ngawi Regency after the Covid-19 pandemic, as well as to find out the difference in the better influence between Hypnotherapy Direct Suggestion technique and Regression technique on the stress level of male athletes and martial arts female athletes in Ngawi Regency after the Covid-19 pandemic. This research is a study using quantitative methods with comparative study techniques. Comparative Research is a study conducted to find out whether two or more of the two groups there are differences in the aspects or variables studied. The results showed that the influence of Hypnotherapy direct suggestion technique and hypnotherapy regression technique on the stress level of male and female athletes of martial arts in Ngawi Regency after the Covid-19 pandemic, as well as a better influence of Hypnotherapy Direct Suggestion technique and compared to Regression technique on the stress level of male athletes and martial arts female athletes in Ngawi Regency after the Covid-19 pandemic.